Women's leadership in cooperative and social movement in the issue of food waste: Evidence from Bandung City - Arry Bainus; Dina Yulianti; Deasy Silvya Sari; Virtuous Setyaka; Wa Ode Kodrat Rahmatika (World Development Sustainability)
Food waste is a critical global issue with significant environmental, economic, and social implications. In Indonesia, one of the world’s largest food-wasting countries, urban centers such as Bandung City face growing challenges in managing household food waste. The limited capacity of municipal authorities has given rise to grassroots initiatives, including the women-led Wahana Usaha Jaya (WUJ) Cooperative. This study investigates how women's leadership within WUJ contributes to behavioral change in households and mobilizes community participation in food waste management.Drawing on qualitative data, this research addresses three questions: (1) how women’s leadership influences household food waste behavior, (2) what leadership strategies are used by WUJ to engage communities, and (3) how socio-cultural and economic contexts shape the effectiveness of these strategies. The findings show that WUJ’s leadership—rooted in spiritual motivation, economic empowerment, and relational engagement—effectively promotes waste reduction practices, especially among women. The cooperative employs hybrid strategies that combine formal coordination with informal, value-based education and demonstrative leadership.Bandung’s socio-cultural landscape, shaped by religious values and a history of environmental crises, enhances the resonance of WUJ’s approach, though infrastructural and institutional barriers remain. The study concludes that women-led, community-based cooperatives can offer inclusive and context-sensitive models of urban environmental governance. Empowering grassroots women leaders is vital for advancing sustainability and food security at the household level in the Global South.